Pengaruh Model Pembelajaran Kooperatif Tipe Two Stay Two Stray (TSTS) terhadap Efikasi Diri dan Hasil Belajar Siswa pada Materi Asam Basa Kelas XI SMA - Hasibuan, Anisya Humaida; Dalimunthe, Makharany (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
The purpose of this study was to determine the significant effect of the Two Stay Two Stray (TSTS) cooperative learning model on students' self-efficacy and learning outcomes, and to determine the correlation between self-efficacy and learning outcomes at SMA Swasta Cerdas Murni. The research sample was taken using a cluster sampling technique, namely class XI IPA 3 as the experimental class and XI IPA 1 as the control class. The instruments used were objective tests to measure learning outcomes and non-test questionnaires to measure self-efficacy. Data analysis was carried out through normality, homogeneity, linearity tests, and hypothesis tests using independent sample t-tests and correlation tests. The results showed that the average self-efficacy and student learning outcomes increased significantly after learning. The N-Gain value of self-efficacy in the experimental group was 0.5486 while the learning outcomes were 0.8212, both of which were higher than the control group. For learning outcomes, the N-Gain value of the experimental class (0.8212) was also higher than the control class (0.7515). The t-test results showed a significant difference between the experimental and control groups in terms of self-efficacy and student learning outcomes (p < 0.05). Furthermore, there was a significant correlation between self-efficacy and learning outcomes (p = 0.001). Thus, TSTS-based learning has been proven effective in improving student self-efficacy and learning outcomes, and there is a strong positive relationship between the two variables.